The Effect of Extraction Method on Catechin Levels in Green Tea (Camellia sinensis L.) Extract by TLC-Densitometric - Aktsar Roskiana Ahmad; Bahria Bahria; Harti Widiastuti (Faculty of Pharmacy, Universitas Muslim Indonesia, 2022)
Green tea (Camellia sinensis L.) is one of the most widely used plants in Indonesia. Green tea (Camellia sinensis L.) is rich in catechins which have many benefits including antioxidants, anticancer, can reduce stress, and reduce cholesterol levels in the blood. This study aims to determine the levels of catechins in Green Tea (Camellia sinensis L.) extract with various extraction methods. Each sample was extracted by maceration, microwave and infusion using aquadest solvent and the extract obtained in Freeze Drying. Qualitative analysis using 1% FeCl3 reagent, positive catechins are indicated by a color change to blackish blue and quantitative analysis using TLC-Densitometry. The results showed the catechin content of the extract by maceration method was 331 mg/g